2020
DOI: 10.3390/app10103392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Effects of Rock Physical Properties Changes from Freeze–Thaw Weathering in Ny-Ålesund Region: Part 2—Correlations and Prediction of Weathered Properties

Abstract: From the examination of rock physical parameters’ changes of compressive strength, shore hardness, water absorption, P-wave velocity with increasing freeze–thaw cycles, correlations of these parameters were investigated. Rock samples were collected from Ny-Ålesund region in Norway. As compressive strength and shore hardness inherently have high uncertainties due to inhomogeneous rock composition and internal fissures and cracks, only the relationship between water absorption and P-wave velocity revealed high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Where, (ɣ d ) was decreased 5.8%, (η) increased 99.8 %, (WA) increased 99.9 % and finally (UCS) decreased 27.1 %. Reality, the negative changes in of these measurements affected rock body inherently have attributed essentially to the flaws or the presence of small cracks, in addition to the relative orientations between major flaws and loading directions as argued previously by Fookes et al [118] and Keunbo et al [119] in their studies. Furthermore, it be resulted due to the alternative cycles of frosting and desolation actions [120], or to the weakening of the bonding strength at rocks interface that influences the lifespan of rocks [121].…”
Section: Discussionmentioning
confidence: 71%
“…Where, (ɣ d ) was decreased 5.8%, (η) increased 99.8 %, (WA) increased 99.9 % and finally (UCS) decreased 27.1 %. Reality, the negative changes in of these measurements affected rock body inherently have attributed essentially to the flaws or the presence of small cracks, in addition to the relative orientations between major flaws and loading directions as argued previously by Fookes et al [118] and Keunbo et al [119] in their studies. Furthermore, it be resulted due to the alternative cycles of frosting and desolation actions [120], or to the weakening of the bonding strength at rocks interface that influences the lifespan of rocks [121].…”
Section: Discussionmentioning
confidence: 71%
“…Under the freeze-thaw weathering cycle effect, the change in rock mechanical properties is caused by the deterioration of the internal pore structure. Therefore, many researchers [25][26][27][28][29][30] have conducted much research through indoor experiments, numerical simulations, damage models, etc. Jiang [31] studied the response mechanism of two kinds of marble microstructures to the dynamic cyclic impact under the condition of freeze-thaw weathering cycles, and he found that under the cyclic dynamic impact, the two marble types exhibited the same trend: the porosity gradually decreased, the pore size continuously decreased, the pore structure tightened, and the permeability weakened.…”
Section: Introductionmentioning
confidence: 99%